Fibrolipoma of the Buccal Mucosa: A Case Report and Review of the Literature - Masayasu Iwase; Naotaka Saida; Yoko Tanaka (Hindawi Limited, 2016)
Lipomas are common benign soft tissue neoplasms derived from mature adipose tissue. However, they rarely arise in the oral cavity. Fibrolipoma is a histological variant of lipoma that mainly affects the buccal mucosa and causes functional and cosmetic issues. This article describes the case of a 71-year-old male with a fibrolipoma of the left buccal mucosa and a review of previous articles about fibrolipoma.